2018
DOI: 10.1021/acsenergylett.8b01562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surfaces on Photoinduced Halide Segregation in Mixed-Halide Perovskites

Abstract: Photoinduced halide segregation currently limits the perovskite chemistries available for use in high-bandgap semiconductors needed for tandem solar cells. Here, we study the impact of post-deposition surface modifications on photoinduced halide segregation in methylammonium lead mixed-halide perovskites. By coating a perovskite surface with the electron-donating ligand trioctylphosphine oxide (TOPO), we are able to both reduce nonradiative recombination and dramatically slow the onset of halide segregation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
260
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(287 citation statements)
references
References 54 publications
11
260
0
Order By: Relevance
“…Obtained E a,forward -values are consistent with prior studies of ion migration in perovskite materials, where Br -(I -) vacancy activation energies between 0.09 and 0.27 eV (0.08 and 0.58 eV) have been found [29,[45][46][47][48]. This suggests vacancy-mediated anion transport, corroborating prior suggestions made [20,[40][41][42]49]. The Arrhenius dependence leads to a functional k forward,abs expression of:…”
Section: Temperaturesupporting
confidence: 88%
See 1 more Smart Citation
“…Obtained E a,forward -values are consistent with prior studies of ion migration in perovskite materials, where Br -(I -) vacancy activation energies between 0.09 and 0.27 eV (0.08 and 0.58 eV) have been found [29,[45][46][47][48]. This suggests vacancy-mediated anion transport, corroborating prior suggestions made [20,[40][41][42]49]. The Arrhenius dependence leads to a functional k forward,abs expression of:…”
Section: Temperaturesupporting
confidence: 88%
“…At the very least, the studies suggest that perovskite film surfaces (or photogenerated carrier proximity to surface defects/grain boundaries) influence halide segregation. This is supported by Belisle and colleagues [49] who have recently found that passivating MAPb(I 1-x Br x ) 3 surfaces using Lewis bases suppresses halide segregation. More about this study will be discussed shortly in the models section of this review.…”
Section: Anion Vacanciesmentioning
confidence: 66%
“…However, a slight decrease of the absolute EQE with increasing bandgap can be recognized even at wavelengths around 430 nm for which the absorptance in the perovskite absorbers is the same for all bandgaps (Figure 2b; Figure S13, Supporting Information). This effect might be ascribed to poorer charge extraction properties in Br‐rich semitransparent PSCs due to energetic misalignment and/or enhanced carrier trapping, [ 83,84 ] thus, further limiting the achievable PCE for wider bandgaps.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3,52,69,73,74 ] A common issue is photo‐induced phase segregation and subsequent funneling of charge carriers into iodide‐rich lower bandgap regions, [ 75 ] acting as radiative recombination centers. [ 68,69,74–80 ] In addition, a higher density of defect states [ 41,79,81,82 ] and stronger interfacial recombination (e.g., due to energy level offsets) [ 51,79,83–87 ] have been proposed to increase non‐radiative recombination losses. Finally, the concentration of vacancy defects and strength of phase segregation seem to be directly linked to each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation